Specific Characteristics of the Development of Gastronomy Tourism in Uzbekistan (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In the article, issues such as television programs and shows, use of social networks, use of new technologies in the development of gastronomic tourism in Uzbekistan were considered, and world experiences were studied.